Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0067-001 HVT/FC/117. Secretary's. 24th December, 1937. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society, Ltd 1, Balloon Street, MANCHESTER 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. Confirming my telephone conversation of this morning I note that for the goods sent by the s.s. Hartbridge the insurance figure is £10.5.0d per cent. In regard to the £2,000 worth of sugar and the ships biscuits which are already on order, you will be aware that suggestions have been discussed as to how milk may be sent to Spain in conjunction with the Co-operative Union. Should any arrangement be arrived at on this matter we should be agreeable to supplies of sugar and biscuits being sent through that channel, but if you feel that satisfactory arrangements could be made for the goods to go by a ship leaving for Barcelona at an early date perhaps you would advise us as to the possibilities. Time is an important factor and I think the best thing we can do is to ask you to make enquiries as to the best possible arrangements for early despatch and let us have your observations. With best wishes for the New Year, Yours sincerely, Assistant Secretary. 292/946/29/67